2016 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2016
DOI: 10.1109/smc.2016.7844316
|View full text |Cite
|
Sign up to set email alerts
|

Spatial filters yield stable features for error-related potentials across conditions

Abstract: Abstract-Error-related potentials (ErrP) have been increasingly studied in psychophysical experiments as well as for brainmachine interfacing. In the latter case, the generalisation capabilities of ErrP decoders is a crucial element to avoid frequent recalibration processes, thus increasing their usability. Previous studies have suggested that ErrP signals are rather stable across recording sessions. Also, studies using protocols of serial stimuli presentation show that these potentials do not change significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Furthermore, the elicited ErrPs were also stable across the three recording sessions (Fig. 3), in line with previous findings (8, 18, 37). On average, 46 and 30 days elapsed between consecutive sessions, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the elicited ErrPs were also stable across the three recording sessions (Fig. 3), in line with previous findings (8, 18, 37). On average, 46 and 30 days elapsed between consecutive sessions, respectively (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…To build the individual decoders, ErrPs were segmented into epochs in the time window of [0.2, 0.8] s with respect to the onset of the visuomotor rotation. Firstly, to enhance the signal-to-noise ratio of the EEG, we applied a spatial filter based on canonical correlation analysis (CCA) (37, 62). This spatial filter method transforms the averaged ErrPs to a subspace containing different ERP components (63).…”
Section: Methodsmentioning
confidence: 99%
“…Although the use of spatial filters for the analysis of ERPs is not as common as for the analysis of sensorimotor rhythms, different studies have shown their advantage [49,50,63]. In particular, the methods CCA and xDAWN have been reported to yield systematic increases in classification performance of time-locked ERPs [50,63], with a slightly superiority of CCA.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of this cut-off frequency was based on previous studies showing the main oscillatory signature of ErrP appears in the theta band [11,17] and the results of the time-frequency analysis. To further enhance the signal-to-noise ratio (SNR) while reducing the number of source signals, we applied a spatial filter based on canonical correlation analysis (CCA) to EEG signals within the range of (0.2, 1.0) s with respect to the onset [49,50]. The choice of the time window was determined based on the grandaveraged signals exhibiting electrophysiological difference between the correct and erroneous trials, as shown in figure 3, which is similar to the previous studies performing synchronous classification analysis [26,35,51].…”
Section: Synchronous Classificationmentioning
confidence: 99%
“…If k number of features are extracted from each electrode, then increasing the number of electrodes (say, from 1 to m) will increase the dimension of the feature vector (dimension will increase to k m ⁎ ). Therefore to find an optimal number of electrodes that carry the most discriminative information between correct and error events spatial filtering methods such as Fishers' beamforming [22], xDAWN [23], Canonical Correlation Analysis (CCA) [24] are employed. However, the spatial filter design often involves solving an optimization problem that is generally computationally intensive.…”
Section: Introductionmentioning
confidence: 99%